2019
DOI: 10.21037/jtd.2019.07.28
|View full text |Cite
|
Sign up to set email alerts
|

A new technology for reducing anastomotic fistula in the neck after esophageal cancer surgery

Abstract: Background: To explore the risk factors and prevention methods of cervical mechanical anastomotic fistula and stenosis after the radical resection of esophageal cancer. Methods: From March 2018 to November 2018, 128 patients undergoing mechanical anastomosis of esophageal cancer were selected from the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…The usefulness of tissue sealant at anastomosis sites is unclear. 17 20 Polyglycolic acid (PGA) sheets (Neoveil ® ; Gunze Co., Tokyo, Japan) are a new type of hemostasis reinforcement material, which promotes tissue sealing and prevents leakage. PGA sheets have been reported to reduce the rates of pancreatic fistula 18 and cervical anastomotic fistula in patients with esophageal cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The usefulness of tissue sealant at anastomosis sites is unclear. 17 20 Polyglycolic acid (PGA) sheets (Neoveil ® ; Gunze Co., Tokyo, Japan) are a new type of hemostasis reinforcement material, which promotes tissue sealing and prevents leakage. PGA sheets have been reported to reduce the rates of pancreatic fistula 18 and cervical anastomotic fistula in patients with esophageal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…PGA sheets have been reported to reduce the rates of pancreatic fistula 18 and cervical anastomotic fistula in patients with esophageal cancer. 20 Few studies in urologic surgery have tested the efficacy of PGA sheets for hemostasis after partial nephrectomy. 19 Further studies are needed to determine the role of bio-absorbable material in reducing fistula formation in patients undergoing urologic surgery.…”
Section: Discussionmentioning
confidence: 99%
“…The usefulness of tissue sealant at anastomosis sites is unclear [17][18][19][20]. Polyglycolic acid (PGA) sheets (Neoveil ® ; Gunze Co., Tokyo, Japan) are a new type of hemostasis reinforcement material, which promotes tissue sealing and prevents leakage.…”
Section: Discussionmentioning
confidence: 99%
“…Polyglycolic acid (PGA) sheets (Neoveil ® ; Gunze Co., Tokyo, Japan) are a new type of hemostasis reinforcement material, which promotes tissue sealing and prevents leakage. PGA sheets have been reported to reduce the rates of pancreatic fistula [18] and cervical anastomotic fistula in patients with esophageal cancer [20]. Few studies in urologic surgery have tested the efficacy of PGA sheets for hemostasis after partial nephrectomy [19].…”
Section: Discussionmentioning
confidence: 99%
“…were included in this study.2 cases were were excluded due to tumor invasion, 11 cases were excluded due to lack of data, and 2 cases were excluded due to simultaneous total gastrectomy.All patients underwent preoperative routine examination and evaluation, including complete blood count, biochemical examination of liver and kidney function, blood coagulation examination, pulmonary function examination, b-ultrasound of liver and gallbladder urinary system, b-ultrasound of the heart, chest and upper abdomen enhanced Computed Tomography(CT), skull CT, bone scan, electrocardiogram, gastroscope and barium meal examination.If the patient's general condition allowed, neoadjuvant chemotherapy was performed after discussion in the thoracic department. The chemotherapy drug was cisplatin followed by the next drug: paclitaxel, docetaxel and gemcitabine.One day before the operation, department experts and anesthesiologists discussed and assessed the risks of the operation and preliminarily formulated the operation method.All the patients included in this study underwent mixed minimally invasive esophagectomy including laparoscopy, thoracoscopy and open surgery.The recurrent laryngeal nerve and thoracic duct should be protected during mediastinal stage.The reconstruction of digestive tract was performed by replacing esophagus with tubular stomach, The location of the anastomotic site was determined by neck or chest anastomosis depending on the patient's condition and tumor location.Finally, the anastomotic site was wrapped around with greater omentum or high molecular tissue material to prevent anastomotic leakage (19).Postoperative pathology showed that all the 177 patients in this group had squamous cell carcinoma and negative resection margin (R0 resection).The rst day after the operation, the patient was examined by bedside chest radiograph.Complete blood count, electrolyte examination,liver and kidney function tests were performed on the 1st and 3rd day after the operation.Chest CT was scheduled for the third day after surgery.…”
Section: Introductionmentioning
confidence: 99%